2020
DOI: 10.7196/samj.2020.v110i12.14582
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of incidental colorectal polyps in patients undergoing colonoscopy at a South African tertiary institution

Abstract: Colorectal cancer (CRC) is the second most common cancer in women, and the third most common in men, and accounts for 10% of all cancers worldwide. [1] Classically, CRCs arise from adenomas, through the adenoma-carcinoma sequence described by Fearon and Vogelstein. [2] The prevalence of adenomas in a population generally correlates with the incidence of CRC. The latter varies widely across the globe, with the USA and Western European countries reporting age-standardised incidence rates per 100 000 population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In contrast, a review of colonoscopy records conducted in Cape Town, South Africa showed that of 246 polyps, 10.6% were hyperplastic and only 1.6% were serrated adenomas. The latter were not further subclassified [ 49 ]. In an Egyptian study, HPs accounted for 15% of non-adenomatous polyps, the majority being hamartomatous.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a review of colonoscopy records conducted in Cape Town, South Africa showed that of 246 polyps, 10.6% were hyperplastic and only 1.6% were serrated adenomas. The latter were not further subclassified [ 49 ]. In an Egyptian study, HPs accounted for 15% of non-adenomatous polyps, the majority being hamartomatous.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the second study, from an academic state institution, Groote Schuur Hospital, Cape Town, reviewed 992 colonoscopies in people at average risk of colorectal cancer. [7] The ADR in this study was 12% (18% in white and Asian patients (16/103 and 2/13, respectively), 13% (95/757) in the mixed-race population and 5% (6/119) in black South Africans). Although these studies are hospital based, and not truly reflective of the typical healthy adult population for which ADR is regarded as the benchmark, they provide a solid basis for clinical practice in SA and the rest of Africa.…”
Section: Guest Editorialmentioning
confidence: 45%
“…In this issue of SAMJ, two studies for the first time report information assessing the quality of colonoscopy in the public and private sectors. [6,7] It is heartening that the CIR in both studies meets international targets. However, the proportion of examinations with adequate bowel preparation falls short of recommendations.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Generally, the adenoma detection rates among patients seeking colonoscopy are lower across the African continent. [9][10][11] It is more likely to diagnose CRC in black patients presenting for colonoscopy, despite the paradoxical low polyp detection rates. This is because the black African population are more likely to present for colonoscopy after onset of alarm symptoms.…”
Section: Epidemiology Risk Factors and Geneticsmentioning
confidence: 99%